Evaluation of the Lower Devonian Tadrart Reservoir in X Oilfield, Ghadames Basin, Libya (Sebha University Conference Proceedings, 2025)
The Ghadames Basin situated in northwestern Libya and extending into Algeria and Tunisia contains up to 6,000 square kilometers of Paleozoic and Mesozoic. Reservoir evaluation is of great importance in the oil and gas industry, as it helps understand the characteristics of the reservoir and predict the behavior of the reservoir over time The focus of this study deals with the sedimentology analysis and reservoir evaluation of Lower Devonian Tadrart Sandstone, Petrel software. Techlog software and detailed core analyses were integral tools used for the study. The findings reveal that Tadrart-D1 locally subdivided into sub zone Tadrart-D1a.Tadrart-D1aSH and Tadrart-D1b, Tadrart-D1b represent the main reservoir composed of estuarine, tidal sand flats and shore face deposits. The Tadrart Reservoir exhibits favorable qualities. A thickness map generated using significant variability in the gross formation thickness, ranging from 133 to 310 feet. Petrophysical analysis estimates the net pay thickness of the Tadrart-D1b unit between a few feet and 60 feet, with porosity reaching up to 16%, water saturation peaking at 49%, and shale volume measuring up to 16%. For the Tadrart-D2 unit, the maximum thickness reaches 45.5 feet, with porosity varying between 7% and 17%, water saturation between 35% and 56%, and similar depositional characteristics. Core descriptions compared with log signatures and petrophysical results allowed for the accurate identification of depositional environments associated with these units.